Development of PMRI Module in NTT Local Cultural Context to Improve Numeracy Literacy - Julindra Lesmana Baria; Agustin Fatmawati; Nia Kurniaty Rukman (Inovasi Matematika)
This research aims to develop a PMRI-based learning module with the context of NTT to improve students' numeracy literacy. This research refers to a 4D model. The data collection techniques used are observation, tests and questionnaires. The data analysis techniques used are qualitative and quantitative analysis to get a more comprehensive picture of the effectiveness of the local culture-based PMRI module from various perspectives, both numerical and narrative. The research stage of the define stage, namely analyzing the applicable curriculum and analyzing student needs. The design stage is product design, including substance and layout. The develop stage, validation by experts to evaluate the feasibility of the product developed before being tested on the real subject. Next is the disseminate stage, namely dissemination by conducting product trials. The trial was carried out on randomly selected grade VII students. The average result of students' numeracy literacy ability at the time of the pretest was 43.86. This score increased as seen from the average numeracy literacy ability in the post test, which was 86.70. This shows that PMRI-based modules using local cultural contexts can improve students' numeracy literacy skills.